Nutritional quality of adult Eriocheir sinensis from the Yangtze River and Yellow River populations cultured in ponds at the Yellow River estuary area - Minghui Shang; Chen Tang; Yunfei Sun; Yongxu Cheng (Aquaculture and Fisheries)
In this study, Chinese mitten crabs from the Yangtze River and Yellow River were cultured in ponds in the Yellow River estuary, and their edible tissue proportion, edible yield, and nutrient composition were compared. No significant differences were found in the total edible rate and proximate composition of edible tissues between the populations of Chinese mitten crabs from the Yangtze River and Yellow River. The content of C18:1n9 and total mono-unsaturated fatty acids (∑MUFA) in the female hepatopancreas of the Yangtze River population were significantly higher than those of the Yellow River population (P < 0.05), whereas the contents of total n-3 poly-unsaturated fatty acids (∑n-3PUFA) were significantly lower than those of the Yellow River population (P < 0.05). The content of C22:6n3 (DHA) in female gonads of the Yellow River population was significantly higher than that in the Yangtze River population (P < 0.05). In the muscle, the DHA content in females of the Yellow River population was significantly higher than that of the Yangtze River population (P < 0.05), the total content of highly unsaturated fatty acids (∑HUFA) was significantly higher than that of the Yangtze River population (P < 0.05), and the Σ HUFA content in males was significantly higher than that in the Yangtze River population (P < 0.05). In the muscle, the contents of threonine, serine, glutamic acid, alanine, and proline of the Yangtze River population were significantly higher than those in the Yellow River population (P < 0.05), regardless of sex. The average essential amino acid score of the muscles in the Yangtze River population was higher than that of the Yellow River population. In conclusion, there was no significant difference in the total edible rate and proximate composition of edible tissues between the two populations of the Yangtze River and the Yellow River after culture in the Yellow River estuary area, but there were some differences in the fatty acid composition of the edible tissue and the amino acid composition of the muscle, which might be related to genetic factors.